CT pulmonary angiography: optimising acute thoracic imaging by fixed-timing contrast medium delivery with a modified breathing instruction. Issue 3 (March 2023) - Brolund-Napier, C.N.; ffrench-Constant, A.E.; Neumann, S.; Paull, J.C.; Fenton, N.K.; Jones, C.A.; Lyen, S.; Manghat, N.E.; Hamilton, M.C.K.
Abstract : AIM: To compare the thoracic vascular opacification achieved using the standard bolus-tracking protocol (BTP) with a fixed-timing protocol (FTP) with a modified breathing instruction during computed tomography pulmonary angiography (CTPA) examinations. MATERIALS AND METHODS: A single-centre review of CTPA examinations performed between July 2018 and January 2019 using the BTP or FTP and weight-based contrast dosing of 20 mg iodine/kg body weight/s for 20 seconds at 100 kV tube potential. Radiodensity (in Hounsfield units) was analysed in the right ventricle, main pulmonary artery (MPA), left atrium, left ventricle, and ascending and descending thoracic aorta (DTA). A p -value of <0.05 was considered significant. RESULTS: Of 782 examinations, 88 BTP and 90 FTP examinations were included. Mean attenuation of the MPA was similar in the FTP (396 ± 106 HU) and BTP (362 ± 119 HU; p =0.06); however, good-quality (≥250 HU) MPA opacification was achieved in more FTP examinations (87/90, 96.7%) compared to the BTP (73/88, 82.9%; p =0.002). Mean attenuation of the DTA was better in the FTP (325 ± 72 HU) than the BTP (228 ± 75 HU; p <0.0001), with good-quality opacification (≥250 HU) in 76/90 (84.4%) FTP examinations compared with 36/88 (40.9%) BTP examinations ( p <0.001). CONCLUSION: The FTP achieves better opacification of the MPA and DTA compared to the BTP.